Influence of Flipped Classroom and Social Engagement on Vocational Students’ Speaking Performance - Reflianto, Farida Ariani,Ismail Makki (International Conference on Industrial Revolution for Polytechnic Education, 2021)
In recent years the model flipped classroom have widely been adopting to support pedagogy. This research analyzed the influence of flipped classroom model and students’ social engagement in the vocational class. Method of study was experimental-quantitative research with survey methods. Subject of the research were eleventh grade students of State Vocational School Number 2 Padang as many as 60 people. The data of Students’ social engagement were collected by using questionnaires with 5-point Likert scale and speaking performance data were collected by using Oral English Competence Test. Analysis of data used multiple linear regression tests. Finding of the research reported that implementation of flipped classroom model to strengthen Students’ social engagement in the line of socialization ability; personal communication ability and self-control to cooperate with other have significant relation with students’ speaking performance. English teacher can utilize the flipped classroom model to foreign language learner class to improve students’ speaking performance by strengthening the social engagement.